2018
DOI: 10.1161/atvbaha.118.311199
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ceramides

Abstract: Objective- Ceramides are sphingolipids involved with cellular signaling. Synthesis of ceramides occurs in all tissues. Ceramides accumulate within tissues and the blood plasma during metabolic dysfunction, dyslipidemia, and inflammation. Elevations of ceramides are predictive of cardiovascular mortality. We sought to verify the utility of plasma concentrations of 4 ceramides: N-palmitoyl-sphingosine [Cer(16:0)], N-stearoyl-sphingosine [Cer(18:0)], N-nervonoyl-sphingosine [Cer(24:1)], and N-lignoceroyl-sphingos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(122 citation statements)
references
References 26 publications
7
107
1
7
Order By: Relevance
“…Thus, most studies have focused on the more prevalent SMs and ceramides containing the double bond in the sphingoid base backbone. In fact, ceramides with C16:0, C18:0, C20:0, and C24:1 acyl chains are currently the subject of considerable interest because they have been linked to insulin resistance (26) and risk of cardiovascular disease and mortality (40). While our association between dihydro-SM and CRP is novel, the association with c-peptide is consistent with findings for other sphingolipids and suggests that the dihydrosphingolipids may affect insulin secretion and metabolic health as well.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, most studies have focused on the more prevalent SMs and ceramides containing the double bond in the sphingoid base backbone. In fact, ceramides with C16:0, C18:0, C20:0, and C24:1 acyl chains are currently the subject of considerable interest because they have been linked to insulin resistance (26) and risk of cardiovascular disease and mortality (40). While our association between dihydro-SM and CRP is novel, the association with c-peptide is consistent with findings for other sphingolipids and suggests that the dihydrosphingolipids may affect insulin secretion and metabolic health as well.…”
Section: Discussionsupporting
confidence: 83%
“…Recent cardiovascular studies have consistently shown an increased risk of adverse vascular events and mortality in individuals with increased ratios of long-chain to very long-chain ceramides in plasma. 5,17,[31][32][33] In a murine model of ceramide synthase 2 haploinsufficiency, a reduction in levels of very long-chain (C22:0 and C24:0) ceramides and a compensatory increase in levels of longchain ceramides (C16:0) was noted, resulting in an increased susceptibility to insulin resistance and hepatocyte apoptosis. 30 Given the role of ceramides in pancreatic b-cell dysfunction, insulin resistance and vascular reactivity, 34 increased cardiometabolic risk could potentially mediate the association with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients (n = 24) had no evidence of lymph node metastases. 34.1%, and 13.6% of cases at the time of diagnosis, respectively. In the vast majority of patients (95.4%), the depth of tumors was T2 and T3, i.e., 34.0%, and 61.4% of all cases, respectively.…”
Section: Patient Demographicsmentioning
confidence: 96%